Condition Factor and Gonadosomatic Index Study of Nilem (Osteochilus hasselti) Catch in Teluk Lake, Jambi - Yoppie Wulanda; Lauura Hermala Yunita; Septy Heltria; Ester Restiana Endang Gelis; Farhan Ramdhani; Rizky Janatul Magwa (Institut Pertanian Bogor, 2025)
The nilem fish (Osteochilus hasselti) is one of the most easily caught fish in Teluk Lake. Currently, cage farming activity in the lake slightly exceeds the water carrying capacity, which is suspected to affect the life of fish in the lake, including nilem. This study aimed to determine the condition factor and Gonadosomatic Index (GSI) of the nilem catch in the lake. This study was conducted from August to September 2023 in Teluk Lake. This research used a survey method with simple census sampling techniques. The analysis of the length-weight relationship of nilem fish obtained from Teluk Lake showed a positive allometric relationship with a value of b = 3.7148. It showed that the increase in body weight of nilem fish was not linear with the increase in length. The catch results by fishermen for nilem fish found a male-to-female sex ratio of 1:2.15, with 90% of the captured fish in a mature gonad condition. The GSI for females ranged from 3.20% to 8.33% and for males, from 0.03% to 28.89%. The first maturation size (Lm) for male fish was 125.847, with a size class range of 116–126 mm. For female fish, the first maturation size calculation resulted in 112.996 with a size range in the 104–113 mm class. Lm is smaller than the average size of the captured fish, indicating that it is safe to catch, and there is a low likelihood of recruitment overfishing. Keywords: GSI, Lm, Osteochilus hasselti, positive allometric, Teluk Lake.Top of FormBottom of Form